EDUKASI DAN KAMPANYE KESADARAN LINGKUNGAN TENTANG DAMPAK NEGATIF PENAMBANGAN EMAS ILEGAL DI KECAMATAN TABIR, KABUPATEN MERANGIN, JAMBI - Rahayu, Sri; Hamzah, Hamzah; Tiswiyanti, Wiwik; Rainiyati, Rainiyati; Khaldun, Muhammad Hafidz Ibnu; Ramadhan, Muhammad Gema; Yudi, Yudi (Universitas Mataram, 2025)
Plantation is a strategic sector in Jambi Province, contributing 21.3% to GRDP in 2021. Main commodities, such as palm oil and rubber, dominate exports, but falling prices have prompted farmers to switch to illegal gold mining (PETI). PETI uses mercury, pollutes the Batanghari River, and damages the ecosystem. Damage to agricultural land and health threats from mercury are on the rise. This article aims to inform the importance of education and environmental awareness campaigns about the damage caused by illegal gold mining practices. The method used in this activity was a Focus Group Discussion (FGD) facilitated by a team of lecturers from the University of Jambi, who delivered material on the impacts of illegal mining (PETI). The number of participants involved in this activity was 40 people from the community, 2 people from the Merangin Regency office, 6 lecturers from the University of Jambi, and 2 students. This activity is effective as an initial step in increasing public awareness of the dangers of PETI activities. Community participation is an important component in disseminating information and inviting the public to be more concerned about the environmental impacts of PETI activities. The positive response from the community is shown by the hope that the implementation of activities can be carried out sustainably and involve more parties so that the handling of PETI activities can be carried out in an integrated manner.